Usos e cobertura da terra na APA de Itupararanga: a criticidade da paisagem nas APPs - Pereira, Letícia de Oliveira (2022)
The different land uses and the development of human activities in each territory, depending on the interaction between the elements, condition specific, fragmented and heterogeneous structural arrangements of the landscape, which can interfere with the balance of ecosystems, demanding the implementation of territorial management and planning, such as the consolidation of environmentally protected areas. The Itupararanga Environmental Protection Area was created in 1998 for the conservation of Atlantic Forest remnants and, mainly, for water resources in the State of São Paulo. The conservation of water resources demands an analysis of the interaction and the functional unit between the water element and the other elements of the landscape - vegetation and the slope, for example. Thus, the work was based on the analysis of the landscape in the APPs in each sub-basin of the Environmental Protection Area in relation to the potential for conservation of water resources, making it possible to understand the APPs in a situation of greater criticality. The main stages of the work were: 1. Delimitation of the hydrography and sub-basins by topographic maps from IBGE and MDE from ALOS satellite image; 2. Delimitation of APPs (buffer) of 30m to the channels and 50m to the headwaters of drainage and springs; 3. Obtaining the slope by the MDE; 4. Manual classification of Land Uses and Covers through Google Earth satellite images, scale 1:10,000; 5. Characterization of the landscape in each sub-basin with the quantification of each use and mapped coverage; 6. Characterization of the criticality of the landscape in the APPs of each sub-basin, through the Algebra of Maps by weighting and summing the values between the slopes and the uses and coverages in very high, high, medium, low or very low classification for the conservation potential of water resources, and; 7. Analysis of the similarity between the sub-basins by grouping data in exploratory statistics (hierarchical clustering). The APA has 1/3 of its territory covered by forest remnants, and in all 9 sub-basins, the highest percentage of APP area is classified with very high potential for conservation of water resources, with Sub-basins 6 and 8 present high similarity with each other and the most favorable conditions for conservation, precisely located in areas of conservation of natural resources, according to the APA Management Plan, while Sub-basins 3 and 7 present high similarity among themselves and high dissimilarity in relation to the others, with the highest percentages of APPs with low and very low potential, that is, the most critical areas for the conservation of water resources, focusing on urbanized, agricultural and industrial areas, associated with undulating and heavily undulating reliefs. The multicriteria analysis of landscape elements was useful for the analysis and classification of APPs with the greatest potential for the conservation of water resources in the APA, in addition to highlighting critical areas, which require special attention to territorial management practices and environmental planning.